Penerapan Model Pembelajaran Kooperatif Index Card Match dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran KKPI - Adhi Suarjana, I Kadek; Sudirtha, I Gede; Windu Antara Kesiman, Made (Universitas Pendidikan Ganesha, 2013)
This classroom action research was aimed at [1] improving the students’ learning results in KKPI in class X Analis Kesehatan A of SMK Kesehatan Bali Medika Denpasar and [2] investigating the students’ response in class X Analis Kesehatan A of SMK Kesehatan Bali Medika Denpasar toward the use of model application kooperatif index card match to KKPI subject.This study was a Classroom Action Research which consisted of two cycles. Each cycle consisted of four steps namely planning, action, observation and evaluation, and reflection. The subject of this study was the students in class X Analis Kesehatan A of SMK Kesehatan Bali Medika Denpasar at academic year 2012/2013. The class consisted of 34 students. The objects of this study were [1] students learning results and [2] students response toward the use of model application kooperatif index card match to KKPI subject. The data of students’ learning results in KKPI subject were collected through the test and observation and the data of students responses were collected through questionnaire. The collected data was analyzed by using descriptive analysis.The result of this study showed that the students learning results got improvement. In cycle 1, the mean of students scores was 74.72 and the percentage of students classical success was 61.76%. In cycle 2, the mean of students scores was 81,53 and the percentage of students classical success was 94.12%. Besides, the students responses toward the use of model cooperative index card match to KKPI subject were positive with a mean of 62.